A chitosan based scaffold with enhanced mechanical and biocompatible performance for biomedical applications. (November 2020) - Dong, Xianzhen; Cheng, Qiao; Long, Yanpiao; Xu, Chao; Fang, Honglin; Chen, Yuzhe; Dai, Honglian
Highlights: Immobilizing RGD on chitosan brings to its new functional properties for biomedical applications. Incorporated with PLGA-PEG and β-TCP nanoparticles obtained an enhanced mechanical and biocompatible performance chitosan-based scaffold. The good hydrophilicity and biocompatibility of the composite scaffold provided the RSCs a better property on attachment, viability and proliferation. Abstract: Chitosan exhibiting excellent functional properties was found to be potential in a wide variety of industrial and biomedical applications. The lack of biological activities and the poor mechanical properties somewhat limit its applications. To address these limitations, chemical modification has been proved to be an efficient method. Here, we immobilized arginine-glycine-aspartic acid (RGD) on chitosan molecules and incorporated the chitosan with Poly(L-lactide-co-glycolide)-Poly(ethylene glycol) (PLGA-PEG) and β-tricalcium phosphate (β-TCP) nanoparticles to obtain a chitosan-based scaffold with enhanced mechanical and biocompatible performance. XPS and FT-IR confirmed the successful grafting of RGD peptides onto the chitosan chain. The mechanical properties, hydrophilicity and degradation behaviors of the membrane were characterized by stress-strain, water contact angle, and weight loss, respectively. Cytotoxicity, cellular adhesion, and cellular viability of the scaffolds were studied by MTT assay, cell adhesion, and cell survival experiments, respectively. The advantageous mechanical properties and the hydrophilic surface of the chitosan-based scaffold were achieved by blending with PLGA-PEG. The preliminary biocompatibility studies revealed that all the scaffolds were cell compatible, and the hydrophilic surface was more suitable for cell adhesion. The scaffolds grafted with RGD exhibited high cell adhesion rate than the pure chitosan. The results suggested that the surface hydrophilicity and biocompatibility of the chitosan-based scaffolds play an important role in enhancing cell adhesion and growth.